HUBUNGAN STATUS PERNIKAHAN DENGAN PENERIMAAN VAKSINASI COVID-19 OLEH MASYARAKAT DI KELURAHAN SARIO TUMPAAN KECAMATAN SARIO KOTA MANADO - Doringin, Tirsa (Journal Of Community & Emergency, 2024)
Since the government announced the Covid-19 vaccination in Indonesia, the public has been faced with various dilemmas in implementing this policy. Looking at people's activities on social media, there are still calls from groups who reject the Covid-19 vaccine. In fact, there were 49.9 percent of the total 601 respondents who refused to be the first recipients of the Covid-19 vaccine. The purpose of this study was to determine the relationship between marital status and acceptance of Covid- 19 vaccination by the community. This type of research uses a descriptive analytic research design using a cross sectional study. carried out in Sario Tumpaan Village, Sario District, Manado City from May to December 2021 with a total sample of 388 respondents. Based on statistical tests using Chi-Square, the p-value in this study is 0.000 (<0.05), with this result Ho and the OR value of 3.464, which means that unmarried respondents have a risk of 3.464 times not receiving Covid-19 vaccination compared to respondents who have marry. The conclusion of this study is that the majority of respondents are married, most of the people accept the Covid-19 vaccination and there is a significant relationship between marital status and acceptance of the Covid-19 vaccination by the community.